ANALISIS KORELASI ANTARA LUAS LAHAN SAWAH, PERTUMBUHAN EKONOMI, DAN JUMLAH PENDUDUK DI INDONESIA - Muhammad Yazid; Erni Purbiyanti; Indri Januarti (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2020)
The high rate of conversion of rice fields in Indonesia is the logical consequence of the development of a region. Land will have rather a function of the use which has low towards the economic rent of land use which is able to provide higher economic rents. In addition, an increasing number of people are also believed to further increase the pressure on wetland conversion. This study aims to analyze the correlation between the rice fields area in Indonesia with the development of the region, which is proxied by economic growth, and population. The method used is the literature of the time-series data in 1990-2010, which is sourced from the Central Bureau of Statistics. Data processing method using Pearson Product Moment analysis. The study showed that variables rice-fields area in Indonesia have a strong relationship with the variables economic growth; and conversely, have a weak association with a variable number of the population. This suggests that the development of an area applying pressure on rice fields land use, so that instead of rice-fields function cannot be avoided. Governments need to issue regulations restricting the transfer of rice-fields function.